RELIGIOUS CULTURE IN BUILDING CHARACTER RESISTANCE IN SCHOOLS: A SOCIAL RECONSTRUCTION THEORY PERSPECTIVE - Amir Amir; Hasan Baharun; Siti Fatimatus Sunniyah; Sabran Sabran (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
This study aims to analyze the application of religious culture in building children's character resilience at school through the perspective of social reconstruction theory. This research was conducted at SMAN I Kraksaan Probolinggo, East Java. A descriptive qualitative approach was used in this research in order to obtain accurate and accountable data through observation, interviews, and documentation. The data analysis was carried out in stages, starting with presenting the data, reducing the data, and concluding. The study results show that the application of religious culture in building children's character resilience in schools through the perspective of social reconstruction theory is carried out through externalization, objectivation, and internalization in a planned, systematic and sustainable manner. This research has implications for the importance of strengthening children's character resilience so that they are not easily swayed by the dynamics of the times.